Incorporating LGBTQ Young Adult Literature into the AYA ELA Classroom as a Means to Bring Representation to Underrepresented Groups (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
This article advocates for the incorporation of LGBTQ young adult literature into the AYA ELA classroom as a means to address the lack of representation of LGBTQ individuals in the curriculum. It begins by sharing statistics taken from a nation-wide survey pertaining to discrimination against LGBTQ students in classrooms around the USA. From there it argues for the importance of incorporating young adult literature in the classroom, and explores methods for incorporating LGBTQ young adult literature in the classroom. Finally, it discusses how to address the pressures that may be presented in response to the incorporation of these texts.